Manajemen Nyeri : Senam Dysmenorrhea Dan Abdominal Stretching Dengan Masalah Keperawatan Nyeri Akut Pada Remaja Menstruasi Di Desa Telukan (Indonesian Journal on Medical Science, 2021)
Abstract: Menstruation is periodic vaginal bleeding due to the detachment of the uterine endometrial lining. Based on a preliminary study conducted, 16 of 22 adolescent girls in Telukan village with an age range of 13-20 years experienced moderate to severe menstrual pain. Dysmenorrhea can be overcome with dysmenorrhea exercise and abdominal stretching. The purpose of the study: to describe the management of dysmenorrhea and abdominal stretching exercises with menstrual pain in adolescent girls. The research design is a qualitative research, using a case study with a nursing process approach. The population of this research is adolescent girls who are menstruating in Telukan Village. The sampling technique is non-probability sampling with a purposive sampling approach. Inclusion criteria: adolescent girls aged 13-20 years, menstruating, experiencing menstrual pain on a scale of 4-6, never bleeding between menstruation after getting regular menstrual cycles. The results of the assessment of menstrual pain; holding pain, closing eyes while grimacing, holding stomach, duration of menstrual pain is approximately 15-20 minutes. Blood pressure were 110/70-120/80 mmHg, RR: 19-21 breaths per minute, N: 78-93 times per minute, S: 36.6-36.8Â°C. The nursing diagnosis is acute pain related to biological injury agents (menstruation). Nursing actions for dysmenorrhea and abdominal stretching were carried out for 3 times. General evaluation of dysmenorrhea and abdominal stretching exercises can reduce pain levels from a scale of 5-6 to 2-3. The results of the research on dysmenorrhea and abdominal stretching can reduce the scale of menstrual pain.Keywords: dysmenorrhea exercise, abdominal stretching, dysmenorrheaAbstrak: Menstruasi adalah perdarahan vagina secara berkala akibat terlepasnya lapisan endometrium uterus. Berdasarkan studi pendahuluan yang dilakukan, 16 dari 22 remaja putri di desa Telukan dengan rentang usia 13-20 tahun mengalami nyeri haid sedang sampai dengan berat. Dysmenorrhea dapat teratasi dengan senam dysmenorrea dan abdominal stretching. Tujuan penelitian: mendeskripsikan penatalaksanaan senam dysmenorrea dan abdominal stretching dengan nyeri haid pada remaja putri. Desain penelitian adalah penelitian kualitatif, menggunakan studi kasus dengan pendekatan proses keperawatan. Populasin penelitian adalah remaja putri yang sedang menstruasi di Desa Telukan. Teknik sampling yaitu non-probability sampling dengan pendekatan purposive sampling. Kriteria inklusi: remaja putri usia 13-20 tahun, sedang menstruasi, mengalami nyeri haid skala 4-6, tidak pernah perdarahan antar menstruasi setelah mendapatkan siklus haid teratur. Hasil pengkajian nyeri haid menahan nyeri, memejamkan mata sambil meringis, memegangi perut, durasi nyeri haid lebih kurang 15 - 20 menit. Tekanan darah 110/70-120/80 mmHg, RR: 19-21 kali per menit, N: 78-93 kali per menit, S: 36,6-36,8Â°C. Diagnosis keperawatan adalah nyeri akut berhubungan dengan agen cidera biologis (menstruasi). Tindakan keperawatan senam dysmenorrea dan abdominal stretching dilakukan selama 3 kali tindakan. Evaluasi secara umum dari senam dysmenorrea dan abdominal stretching dapat menurunkan tingkat nyeri dari skala 5-6 menjadi 2-3. Hasil penelitian senam dysmenorrea dan abdominal stretching dapat menurunkan skala nyeri haid.Kata kunci: senam dysmenorrhea, abdominal stretching, dysmenorrhea